Pantomime Di SD Pembangunan Laboratorium UNP: Kegiatan Penyaluran Bakat Teater Siswa Melalui Kegiatan Ekstrakurikuler - Hasyim Asyary; Syeilendra Syeilendra (SENDRATASIK UNP, 2020)
This research aims to describe the implementation of theater talent manifestation activities through pantomime extracurricular at SD Pembangunan Laboratorium UNP, Universitas Negeri Padang, West Sumatra. This is a qualitative research using descriptive analysis method. The main instrument used was the researcher itself and was assisted by supporting instruments such as writing instruments and cellphone cameras. The data were collected through observation, interviews, literature study, and documentation. The data were analyzed by separating primary and secondary data. Then, the contents were grouped and arranged systematically, and finally conclusions were made.The results show that the pantomime extracurricular activities conducted are routinely carried out with the aim of doing performance activities such as in monthly agenda, farewell party, and pantomime competitions. The process of implementing pantomime extracurricular activities begins with various preparation for training sites, materials, and program implementation. Pantomime extracurricular material begins by grouping students into 3 groups: high class group, low class group, and non-active group. Then, it is continued by introducing pantomime in general as well as some examples performed by the trainer. The methods used by the trainer are lecture, question and answer, peer tutoring, and demonstration.